Androgen associated hepatocellular carcinoma with an aggressive course. Issue 9 (September 1991) - Gleeson, D; Newbould, M J; Taylor, P; McMahon, R F; Leahy, B C; Warnes, T W
Abstract : The hepatocellular carcinomas that develop in patients treated with androgens have previously been associated with a benign clinical outcome. We describe a man who developed a hepatocellular carcinoma after 24 years of androgen treatment, whose tumour initially showed partial regression after withdrawal of androgens but subsequently pursued an aggressive and fatal course.